Ultra-broadband frequency responsive sensor based on lightweight and flexible carbon nanostructured polymeric nanocomposites - Zeng, Zhihui (2017)
Strain sensing in an ultra-broadband frequency regime up to 400 kHz is obtained with developed lightweight and flexible carbon nanostructured polymer composites, in a frequency range far broader than any piezoresistive sensor previously reported. Various loadings, from static and low-frequency cyclic stretches, through high-frequency vibration, to ultrahigh-frequency ultrasonic guided waves, are applied for evaluation of the sensors' performance. Diverse content and type of carbon nanofiller, microstructure of the conductive network in the matrix, and electromechanical responses of the nanocomposites under broadband-frequency strain are discussed, in conjunction with dynamic mechanical analysis and a theoretical nanoscale model, to advance insight into the sensing mechanism of the sensors. Implementation of ultrasonic guided wave-based in-situ structural health monitoring using networked sensors made of carbon black/polyvinylidene fluoride nanocomposites indicates the significant application potential of the developed sensor to serve as an ultra-broadband and high-frequency responsive flexible strain sensor.